2017
DOI: 10.1177/0004944117712777
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage assessment method for assessing oral language in early childhood

Abstract: Although the teaching of children's oral language is critical to both their social development and academic success, the assessment of oral language development poses many challenges for classroom teachers. The aim of the study is to develop an approach that: (i) enables teachers to assess oral language in a reliable, valid and comparable manner and (ii) provides information to support targeted teaching of oral language. The first stage of the study applies the method of pairwise comparisons to place exemplars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Perhaps the most focus to date has been on judging and scaling students' writing performances (Heldsinger & Humphry, 2010;Steedle & Ferrara, 2016;van Daal, Lesterhuis, Coertjens, Donche, & De Maeyer, 2016) and students' problem solving in mathematics (Bisson, Gilmore, Inglis, & Jones, 2016;Jones & Inglis, 2015;Jones, Swan, & Pollitt, 2015). Other areas of focus have included peer assessment and feedback (Potter et al, 2017;Seery, Canty, & Phelan, 2012), the assessment of creative performances (Tarricone & Newhouse, 2016), and the assessment of oral narrative performances (Humphry, Heldsinger, & Dawkins, 2017). There has also been some research into the application of pairwise comparisons in setting grade boundaries (Benton & Elliot, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most focus to date has been on judging and scaling students' writing performances (Heldsinger & Humphry, 2010;Steedle & Ferrara, 2016;van Daal, Lesterhuis, Coertjens, Donche, & De Maeyer, 2016) and students' problem solving in mathematics (Bisson, Gilmore, Inglis, & Jones, 2016;Jones & Inglis, 2015;Jones, Swan, & Pollitt, 2015). Other areas of focus have included peer assessment and feedback (Potter et al, 2017;Seery, Canty, & Phelan, 2012), the assessment of creative performances (Tarricone & Newhouse, 2016), and the assessment of oral narrative performances (Humphry, Heldsinger, & Dawkins, 2017). There has also been some research into the application of pairwise comparisons in setting grade boundaries (Benton & Elliot, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this early work, performance descriptors were not provided as a complement to the exemplars. The reliability of judgements using this method, and including performance descriptors, were subsequently investigated for oral language in early childhood (Humphry et al, 2017) and for essay writing in primary students (Humphry and Heldsinger, 2019). The present study extends the previous research to investigate the reliability of the methodology in the context of narrative writing obtained from students aged 5-12.…”
Section: Methods Of Pairwise Comparisonsmentioning
confidence: 65%
“…The aim of the research reported here is to collect empirical evidence about the reliability of teacher judgements of narrative writing assessment using a specific two-stage assessment method that has been used in three previous studies (Heldsinger and Humphry, 2013;Humphry et al, 2017;Humphry and Heldsinger, 2019). In the first stage, a large sample of performances are calibrated using the method of pairwise comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Löfdahl & Hägglund, 2006), use of argumentative and narrative discourse features (e.g. Humphry, Heldsinger & Dawkins, 2017;Zadunaisky Ehrlich & Blum-Kulka, 2014) and functions of language in young children's play (e.g. Tough, 1976).…”
Section: Related Research and Available Oral Language Assessment Toolsmentioning
confidence: 99%